1998
DOI: 10.1016/s0741-5214(98)70022-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of thromboangiitis obliterans (Buerger's disease) by intramuscular gene transfer of vascular endothelial growth factor: Preliminary clinical results

Abstract: Therapeutic angiogenesis with phVEGF165 gene transfer, if instituted before the development of forefoot gangrene, may provide a novel therapy for patients with advanced Buerger's disease that is unresponsive to standard medical or surgical treatment methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
208
0
10

Year Published

2000
2000
2005
2005

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 360 publications
(221 citation statements)
references
References 22 publications
(21 reference statements)
3
208
0
10
Order By: Relevance
“…The clinical utility of gene therapy using the VEGF gene has been recently reported for the treatment of critical limb ischemia and myocardial ischemia. [4][5][6][7][8][9][10][11] Instead of VEGF, other angiogenic growth factors such FGF, HGF and a transcription factor for angiogenesis, HIF (hypoxiainducible factor), have been considered candidates for therapeutic angiogenesis as gene therapy for the treatment of patients with critical limb ischemia. [12][13][14][15][16][17][18][19][20] Although the feasibility of therapeutic angiogenesis using these angiogenic growth factors has been reported in experimental models and human clinical trials, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] there are still unresolved problems such as undesirable side-effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The clinical utility of gene therapy using the VEGF gene has been recently reported for the treatment of critical limb ischemia and myocardial ischemia. [4][5][6][7][8][9][10][11] Instead of VEGF, other angiogenic growth factors such FGF, HGF and a transcription factor for angiogenesis, HIF (hypoxiainducible factor), have been considered candidates for therapeutic angiogenesis as gene therapy for the treatment of patients with critical limb ischemia. [12][13][14][15][16][17][18][19][20] Although the feasibility of therapeutic angiogenesis using these angiogenic growth factors has been reported in experimental models and human clinical trials, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] there are still unresolved problems such as undesirable side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…1 Therefore, novel therapeutic modalities are needed to treat these patients. Recently, the efficacy of therapeutic angiogenesis using VEGF (vascular endothelial growth factor) gene transfer has been reported in human patients with critical limb ischemia [4][5][6][7] and myocardial ischemia. [8][9][10][11] In addition to VEGF, the utility of gene transfer of other angiogenic growth factors such as fibroblast growth factor (FGF) or hepatocyte growth factor (HGF) has been reported to stimulate collateral formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct injection of plasmid encoding VEGF into the peripheral limbs of patients in a Phase I clinical trial demonstrated improved peripheral blood flow, new collateral vessel formation, healing of ischemic ulcers and reduced the need for amputation. [28][29][30] Similarly, Phase I trials evaluating plasmid-or adenovirus-mediated gene delivery of VEGF into the ischemic myocardium of patients found reductions in angina class, reduced need for anginal medication, increased number of collaterals by angiography, improvements in myocardial perfusion and increased exercise treadmill times. 23,[25][26][27] Although these early clinical trials have had limited patient numbers and lacked placebo controls, they have generated enthusiasm for further studies.…”
Section: Discussionmentioning
confidence: 99%
“…Several ongoing clinical studies are utilizing the gene encoding vascular endothelial growth factor (VEGF) to promote revascularization within ischemic tissue. [23][24][25][26][27][28][29][30] VEGF, also known as vascular permeability factor, is a secreted endothelial cell-specific mitogen. 31 VEGF is expressed through alternative splicing giving rise to at least five isoforms coding for proteins of 206, 189, 165, 145, and 121 amino acids.…”
Section: Introductionmentioning
confidence: 99%